Gabon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses impact of the falling oil prices on the Gabon's economy. With oil accounting for roughly 40 percent of its GDP, 45 percent of its government revenues, and nearly 85 percent of its exports in 2014, Gabon's economic growth prospects depend on how it copes with the recent oil-price slumps. Economic performance during major oil-price declines clearly illustrates the vulnerability of Gabon and other oil-dependent countries in sub-Saharan Africa. The recent oil-price slump is bound to generate a major deceleration of Gabon's non-oil economy. Given the strength of the government transmission channel, the authorities should support economic activity (through productive spending) while ensuring fiscal sustainability.